Produção de sentido das práticas pedagógicas na socioeducação - Andrade, Marcia Maria Razera de (2017)
The aim of this research is to study the educational practices developed in two socio-educational units: The São Francisco Socio-Education Centre (CENSE), located in the city of Piraquara-PR and the Socio-Education Centre Curitiba, located in the city of Curitiba-PR. This research aims to analyse the production of meaning in the social education through pedagogical practices in the selected socio-educational institutions. In order to do so, we set out the following specific objectives: to identify the purposes of education in socio-educational institutions according to the modality of Youth and Adult Education; Define the profile of the subjects involved in the teaching and learning process in the social education units studied: students and teachers; analyse the conception of school reported by the adolescents surveyed; to verify the educational practices developed in these socio-educational units. To achieve these objectives, a survey was carried out with the institutions to elaborate the profile of young offenders and the professionals who serve them. A documentary analysis and the production of research instruments were also carried out, such as questionnaires aimed at students and professionals of the studied units, aiming at the apprehension of the purposes of the institution and specificities of the internal dynamics of the socio-educational units, focusing especially on educational practices. The research is justified, since its results may contribute to the training of adolescents during the period of hospitalization and to fill the shortage of output of works under the theme. The research problem is oriented to the reflection on the limits and possibilities of a socio-educational unit for the fulfilment of its fundamental purpose, as foreseen by the legislation, that is, the training of young offenders during their internment process. Among the main theoretical references are Adorno (1999), Altoé (2009), Bauman (2012), Dias (2011), Franco (2015), Spink (1999) and Veiga (1989). The research presents a qualitative approach and as it is being done through documentary and field research, it is expected that the research contributes to indicate advances and challenges related to educational practices in the socio education and the production of meanings of a meaningful education for the life of teenagers.